Black Phosphorus Saturable Absorber for Pulse Generation Using Q-switched Teachnique - Belal Ahmed Hamida; L A Hussein; Sheroz Khan; Mohamed Hadi Habaebi; Ahmad Anwar Zainuddin; T Eltaif; S W Harun (Institute of Advanced Engineering and Science, 2018)
This paper reported a passive Q-switched erbium doped fiber laser (EDFL) using two-dimensional (2D) material of black phosphorus saturable absorber (BP-SA). The maximum output power reached is 3.54 mW, which is generated by pump power of 42.327 mW. The results show that a stable pulse was generated with repetition rate starts at about 9.606 kHz and ends at about 44.72 kHz and very narrow pulse width between 40.01 µs and 9.84 µs and pulse energy 80 nJ. Clearly, the stability of the Q-switched pulse train was achieved because the BP-SA film was inserted in the laser ring cavity.